Sphingosine 1-phosphate signaling in bone remodeling: multifaceted roles and therapeutic potential. (3rd July 2017) - Meshcheryakova, Anastasia; Mechtcheriakova, Diana; Pietschmann, Peter
ABSTRACT: Introduction : Sphingolipids belong to a complex class of lipid molecules that are crucially involved in the regulation of important biological processes including proliferation, migration and apoptosis. Given the significant progress made in understanding the sphingolipid pathobiology of several diseases, sphingolipid-related checkpoints emerge as attractive targets. Recent data indicate the multifaceted contribution of the sphingolipid machinery to osteoclast – osteoblast crosstalk, representing one of the pivotal interactions underlying bone homeostasis. Imbalances in the interplay of osteoblasts and osteoclasts might lead to bone-related diseases such as osteoporosis, rheumatoid arthritis, and bone metastases. Areas covered : We summarize and analyze the progress made in bone research in the context of the current knowledge of sphingolipid-related mechanisms regulating bone remodeling. Particular emphasis was given to bioactive sphingosine 1-phosphate (S1P) and S1P receptors (S1PRs). Moreover, the mechanisms of how dysregulations of this machinery cause bone diseases, are covered. Expert opinion : In the context of bone diseases, pharmacological interference with sphingolipid machinery may lead to novel directions in therapeutic strategies. Implementation of knowledge derived from in vivo animal models and in vitro studies using pharmacological agents to manipulate the S1P/S1PRs axes suggests S1PR2 and S1PR3 as potential drug targets, particularly in conjunction with technology for local drug delivery.